Teachers' Perception and Contribution of School Meals to Nutrient Intake of Kenyan Children in Relation to Recommended Dietary Requirements - Mbijiwe, Jane; Muriungi, Pamella Karambu; Koech, Peter Kibet; M’Rithaa, Mugendi Kanampiu (East African Journal of Agriculture and Biotechnology, 2025)
Background:Information on thecomposition of school meals and their contribution to the nutritional needs of children isscarce. Although teachers are pivotal in the school meals provision process,their perceptions have been ignored.Methods:A cross-sectionalstudy was conducted among 70 school teachers and 200 pupils from 11 public schools. Data collection toolsincluded:a pretested study questionnaire, interview guide, food diary, analysis of school records and observation checklists.Results: Over 77% of school teachersperceived the portion of school meals served to children to be inadequate, 98.6% were of the view that meals lacked dietary diversity,while 95.7%reported meals were not well balanced.These findingshighlightteachers’ contextual awareness ofpoormeal quality;nevertheless,this could be leveraged in having them as advocates for enhanced school meals.About 84.3%of teachersindicatedprovision of school meals was irregular, implyingthat theirfull potential to alleviate short-termhunger, improve attention spans and learning capabilities was not being fully utilised. Meals consisted only two food groups 130 grams of maize (cereals) and 20 grams of beans (legumes), and were low in micronutrients providing only 8.8% of calcium, 22.2% of iron, 17.7% of zinc,while completely lacking in vitamin A and Vitamin C.Need to explore strategies to include more food groups in school meals to enhance dietary diversity and micronutrient adequacies. Current school meals provided 5.8 grams of protein,which was only 76.7% of the daily requirements and did not meet the recommended nutrient needs for energy and carbohydrates, implying children were at increased risk of nutritional deficiencies.Evidenced by findings that 24.0% of the children werestunted.Conclusion:This study highlights theneed to improvethe qualityof school meals,particularly with regard to dietary diversity and nutrient adequacy for protein, carbohydrates, vitamin A, Vitamin C, calcium, iron and zinc.Establishing school gardensand supporting them technically and financially,especially in livestock rearing and the production of fruits and vegetables,could enhance food variety, thereby improving dietary diversity and micronutrient intake of school-goingchildren in Kenya.
Keywords: School Meals; Nutrient Intake; School Age Children; Teachers; Food Insecure